Look out for Rosy! - Graham, Bob (Australia : The Five Mile Press, 1986)
Mike experiences the five senses - but loses his ice-cream cone - when he is greeted by Rosy, his overly enthusiastic dog.
Keywords: Senses -- Juvenile literature; Science - Juvenile Literature